2002
DOI: 10.1007/s10198-002-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

How high are the costs of eating disorders - anorexia nervosa and bulimia nervosa - for German society?

Abstract: Anorexia and bulimia are relatively rare psychogenic illnesses, which nevertheless are of great concern for society since they affect a mostly very young population and are accompanied by a significantly raised mortality risk. This cost-of-illness analysis for eating disorders in Germany considers hospitalization, rehabilitation services, and indirect costs through inability to work and premature death. The cost estimates are based on projections derived from benefit data as listed by health insurance schemes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 14 publications
1
70
1
1
Order By: Relevance
“…[15][16][17][18][19] The evidence base for treatment for AN has been described as "weak," 20,21 and treatment and extended inpatient hospitalizations for weight restoration are costly. 22,23 In sum, the public health impact of AN is considerable, and AN carries substantial morbidity, mortality, and personal, familial, and societal costs.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] The evidence base for treatment for AN has been described as "weak," 20,21 and treatment and extended inpatient hospitalizations for weight restoration are costly. 22,23 In sum, the public health impact of AN is considerable, and AN carries substantial morbidity, mortality, and personal, familial, and societal costs.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Germany found that the cost of hospitalization of patients with AN was markedly higher than the average hospitalization cost (22). Furthermore, some insurance companies refuse payment for such care in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…20 In Germany, costs in 1998 were €65 million for anorexia nervosa and €10 million for bulimia nervosa. 21 In Australia, health care costs of eating disorders were A$22 million in 1993/94. 22 Other cost studies that focused mostly on inpatient care gave highly variable estimates.…”
Section: Discussionmentioning
confidence: 99%